Kommentar der Deutschen Gesellschaft für Thorax-, Herz- und Gefäßchirurgie zum Positionspapier der DGK - Qualitätskriterien zur Durchführung der transvaskulären Aortenklappenimplantation (TAVI) - Cremer, Jochen; Heinemann, Markus K.; Mohr, Friedrich Wilhelm; Diegeler, Anno; Beyersdorf, Friedhelm; Niehaus, Heidi; Ensminger, Stephan; Schlensak, Christian; Reichenspurner, Hermann; Rastan, Ardawan; Trummer, Georg; Walther, Thomas; Lange, Rüdiger; Falk, Volkmar; Beckmann, Andreas; Welz, Armin (The Thoracic and Cardiovascular Surgeon, 2014)
Surgical aortic valve replacement is still considered the first-line treatment for patients suffering from severe aortic valve stenosis. In recent years, transcatheter aortic valve implantation (TAVI) has emerged as an alternative for selected high-risk patients. According to the latest results of the German external quality assurance program, mandatory by law, the initially very high mortality and procedural morbidity have now decreased to approximately 6 and 12%, respectively. Especially in Germany, the number of patients treated by TAVI has increased exponentially. In 2013, a total of 10.602 TAVI procedures were performed. TAVI is claimed to be minimally invasive. This is true concerning the access, but it does not describe the genuine complexity of the procedure, defined by the close neighborhood of the aortic valve to delicate intracardiac structures. Hence, significant numbers of life-threatening complications may occur and have been reported. Owing to the complexity of TAVI, there is a unanimous concordance between cardiologists and cardiac surgeons in the Western world demanding a close heart team approach for patient selection, intervention, handling of complications, and pre- as well as postprocedural care, respectively. The prerequisite is that TAVI should not be performed in centers with no cardiac surgery on site. This is emphasized in all international joint guidelines and expert consensus statements. Today, a small number of patients undergo TAVI procedures in German hospitals without a department of cardiac surgery on site. To be noted, most of these hospitals perform less than 20 cases per year. Recently, the German Cardiac Society (DGK) published a position paper supporting this practice pattern. Contrary to this statement and concerned about the safety of patients treated this way, the German Society for Thoracic and Cardiovascular Surgery (DGTHG) still fully endorses the European (ESC/EACTS) and other actual international guidelines and consensus statements. Only the concomitance of departments for cardiac surgery and cardiology on site can provide optimal TAVI care. This commentary by the DGTHG delineates the data and resources upon which its opinion is based.
Keywords: aortic valve and root; database; heart valve; transapical; percutaneous; TAVI; outcomes; practice guidelines; professional affairs